Air-Gap Interrogation of Surface Plasmon Resonance in Otto Configuration - Yeonsu Lee; Jiwon Kim; Sungmin Sim; Ignacio Llamas-Garro; Jungmu Kim (Micromachines, 2021)
In this study, a micromachined chip in Otto configuration with multiple air-gaps (1.86 μm, 2.42 μm, 3.01 μm, 3.43 μm) was fabricated, and the resonance characteristics for each air-gap was measured with a 980 nm laser source. To verify the variability of the reflectance characteristics of the Otto configuration and its applicability to multiple gas detection, the air-gap between the prism and metal film was adjusted by using a commercial piezoactuator. We experimentally verified that the SPR characteristics of the Otto chip configuration have a dependence on the air-gap distance and wavelength of the incident light. When a light source having a wavelength of 977 nm is used, the minimum reflectance becomes 0.22 when the displacement of the piezoactuator is about 9.3 μm.